In silico identification of genetically attenuated vaccine candidate genes for Plasmodium liver stage - Kumar, Hirdesh; Frischknecht, Friedrich; Mair, Gunnar R.; Gomes, James (Infection, genetics and evolution, 2015)
Genetically attenuated parasites (GAPs) that lack genes essential for the liver stage of the malaria parasite, and therefore cause developmental arrest, have been developed as live vaccines in rodent malaria models and recently been tested in humans. The genes targeted for deletion were often identified by trial and error. Here we present a systematic gene - protein and transcript - expression analyses of several Plasmodium species with the aim to identify candidate genes for the generation of novel GAPs.
Gesehen am 03.06.2020